Amylolytic Fungi in the Ethnic Beer Starter “emao” and Their Beer-Producing Attributes - Boro, Nitesh; Narzary, Diganta (Frontiers in Sustainable Food Systems, 2022)
Naturally occurring autochthonous microbes associated with ethnic beer starters are diverse and important as they play different functional roles in beer fermentations. The study on culturable microbes from the ethnic rice beer starter “emao” of the Bodo community of Assam is limited. Here we isolated and identified the culturable fungal diversity associated with emao and screened them for beer-producing capability from glucose and starch substrates. Based on morphology and molecular characterization, the species identified were Candida glabrata (Cgla_RF2), Cyberlindnera fabianii (Cfab_RF37), Hyphopichia burtonii (Hbur_RF19), Mucor circinelloides (Mcir_RF48), Mucor indicus (Mind_RF25), Penicillium citrinum (Pcit_RF32), Rhodosporidiobolus ruineniae (Rrui_RF4 & Rrui_RF43), Saccharomyces cerevisiae (Scer_RF6), Saccharomycopsis fibuligera (Sfib_RF11), and Wickerhamomyces anomalus (Wano_RF3) among which the relative abundance (RA) of W. anomalus was the highest (24%) followed by C. glabrata and H. burtonii (16% in each). Five (Hbur_RF19, Sfib_RF11, Mind_RF25, Mcir_RF48, and Pcit_RF32) of eleven isolates showed amylase positive in the starch medium. Scer_RF6 showed the highest ethanol tolerance (14% v/v) followed by Hbur_RF19 (12% v/v), Cgla_RF2 (11% v/v) and Wano_RF3 (11% v/v). The amylase-positive strains produced beer-containing ethanol in the range of 3.17–7.3 (% v/v) from rice substrate. Although the rice beer produced by amylase-positive strains showed negligible pH difference, other parameters like ethanol, ascorbic acid, total phenol, and antioxidant properties were varied from beer to beer. Antibacterial activities shown by Mcir_RF48 and Pcit_RF32 against the test bacteria were higher with a 23–35 mm zone of inhibition than the other isolates. The present findings reveal the presence of fungi with antibacterial, amylolytic, ethanol fermenting, and antioxidant producing capacity in emao which could the source for future bioprospection.